(untitled) (Ciencias Veterinarias, 2019)
The reproductive behavior of the mite Varroa destructor in worker and drone brood cells was studied from January to August. The study was conducted using 10 colonies of Africanized honeybees (A. mellifera) from the Tropical Beekeeping Research Center (CINAT), Lagunilla of Heredia, Costa Rica. The research was divided in two phases: a) artificial mites varroa infestation of worker brood cells (n= 732) and b) artificial infestation of drone brood cells with mites taken from the worker cells (n= 362). In addition, the reproductive ability of varroa was compared between worker and drone brood cells (n= 362) and a detail analysis was conducted of the mites that did not reproduce in worker cells and were transferred into drone cells (n= 85). Each cell was examined for mite reproduction 10 days after infestation. The following parameters were measured for foundress female mites: fertility, fecundity, production of fertile females, production of immature offspring, only female or only male production and no reproduction at all. In worker brood cells, fertility rate was 76.9%; however, only 16.5% of the mites produced fertile females with an average of 1.3 ± 0.5 viable daughters. On the other hand, in drone brood cells, fertility rate was 79.3%, and 38.1% of the mites produced fertile females, with an average of 2.1 ± 0.9 viable daughters. Comparing reproductive ability of the mites showed that the fertility rate was similar in both types of brood; however, a considerable amount of the mites produced fertile offspring in the drone cells, while only 13.8% were produced in the worker cells. Furthermore, the production of immature offspring was significantly higher (over 40%) in the worker brood. One of the most relevant findings was that 74.1% of the mites that did not reproduce in worker cells were able to reproduce when transferred to drone cells, which indicates that drone brood is essential to the development and growth of varroa population in Africanized honeybees under tropical conditions.